Functional Characterization of Duck STING in IFN-β Induction and Anti-H9N2 Avian Influenza Viruses Infections - Cheng, Yuqiang; Liu, Yunxia; Shi, Shuduan; Niu, Qiaona; Zhu, Wenxian; Wang, Zhaofei; Ma, Jingjiao; Wang, Hengan; Yan, Yaxian; Sun, Jianhe (Frontiers in Immunology, 2019)
The stimulator of interferon genes (STING) protein has been shown to play a pivotal role in response to both cytosolic RNA and dsDNA to elicit interferon (IFN) production in mammals. However, the role of duck STING (DuSTING) in antiviral innate immunity, especially in anti-RNA virus infection, has yet to be elucidated. In this study, the function of DuSTING in IFN induction and its role in anti-RNA virus infections were studied. DuSTING was amplified via real-time polym erase chain reaction (RT-PCR) from Pekin duck, showing that its cDNA sequence contains an open reading frame (ORF) of 1149 bp and encodes 382 amino acids (aa). Sequence alignment showed that DuSTING protein shares 71.1%, 43.4%, and 33.3% identity with chickens, humans, and zebra fish, respectively. Overexpression of DuSTING in duck embryo fibroblasts (DEFs) strongly activated IFN-β promotor activity. Deletion mutant analysis revealed that the first 42 aa containing the first transmembrane (TM) domains and the last 32 aa containing a part of the C-terminal tail (CTT) are essential for its IFN-β activation. In vitro experiments showed that the mRNA levels of DuSTING and IFNs were all upregulated when the DEFs were infected with H9N2 avian influenza virus (AIV) SH010, while overexpression of DuSTING inhibited the replication of this virus. In vivo studies showed that DuSTING mRNA was widely expressed in different tissues, and was up-regulated in the spleen and lung of ducks challenged with SH010. In conclusion, our results indicate that DuSTING is an essential IFN mediator and plays a role in anti-RNA virus innate immunity.